Plan Individual Fitness Training Programs for Middle-Aged Men (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
An effective training plan is made up individually. It takes into account personal goals, age, body type, diet, class times, and other factors.If you’re already exercising, achieving results, and not getting injured or losing motivation, stick to your chosen system. If there are any failures or you are a beginner athlete, you can use our recommendations.